ナンキョク カンソクタイ ソウビ ウェア ノ ケンキュウ カイハツ - 伊豆原, 月絵; イズハラ, ツキエ; 鮎川, 勝; アユカワ, マサル; Izuhara, Tsukie; Ayukawa, Masaru (2008)
P(論文) 南極地域観測隊員が着装しているウェアを改善するために,観測隊員に聞き取り調査を行った.その結果,極地では動作の種類が多く,作業性を高めるには,「ゆとり量」が一般の衣料に比べ必要であった.また,設営などの作業では,一時的に体温の上昇があることから,汗や顔の周りの霜の対策が重要であることなどを考慮し,開発ウェアには,ポリエステル,ナイロン等の化学繊維(糸)に各種機能(透湿防水,保温,帯電防止など)を付与し,加工した機能性繊維を使用し,透湿・防水・帯電防止・保温性を高めた.また,被服構成(パターン)も考慮した.デザインコンセプトは,「南極観測隊員は,研究者と研究を支えるスタッフ」ということを観察者に示し,「機能性に優れた,知的でスタイルをよくみせるウェア」の研究開発を試みた. The design of wear for Japanese Antarctic Research Expedition (JARE) members was investigated. Wear must be loose-fitting because JARE members perform may kinds of operations. Heat must be able to escape easily. Considering that measures to deal with sweat and frost are necessary, synthetic fibers such as polyester and nylon wear used and treated to increase breathablity, water resistance, resistance to static electricity, and thermal insulation. We produced wear appropriate for JARE members including researchers and research support staff, who need clothing that is both highly functional and in a style appropriate for intellectual pursuits. departmental bulletin paper